2009
DOI: 10.3855/jidc.669
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-Resistant and Extensively Drug Resistant Tuberculosis in Kashmir, India

Abstract: Background: To study the profile of multidrug-resistant tuberculosis (MDR-TB) and extensively drug-resistant tuberculosis (XDR-TB) in tertiary care hospital setting, representing almost the whole affected population in Kashmir valley of India. Methodology: A total of 910 cases of pulmonary tuberculosis were enrolled over four years. Among these, cases of MDR-TB and XDR-TB were meticulously studied for drug susceptibility, treatment, adverse effects profile and overall survival. Results: Fifty-two (5.7%) cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
2
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 12 publications
(11 reference statements)
4
23
2
2
Order By: Relevance
“…treated PTB patients66724.12.34.22.11.53.2LJTertiary hospital (Armed forces)4Rai S P et al, 2007 [27]Ranchi2001–2004Newly diagnosed PTB patients76918.00.41.41.70.43.01.61.6LJTertiary hospital (Armed forces)5Jain A et al (a), 2008 [53]Lucknow2000–2002Combined PTB patients35337.42.00.30.66.019.329.011.0LJTertiary hospital6Jain A et al (b), 2008 [54]Lucknow2002–2004Combined PTB patients68638.229.720.717.827.719.825.513.2LJPrimary, Secondaryand Tertiary healthcare7Rawat J et al, 2009 [55]Dehradun2002–2006Prev. treated PTB patients18062.85.0057.257.2LJTertiary hospital8Datta B S et al, 2009 [56]Kashmir2003–2007Newly diagnosed PTB patients9105.70.9MGIT 960Primary, Secondaryand Tertiary healthcare9Mathuria J P et al (1), 2013 [38]Sawai Madhopur2004–2007Combined PTB patients4822.924.172.0814.5866.677.14LJDistrict...…”
Section: Resultsmentioning
confidence: 99%
“…treated PTB patients66724.12.34.22.11.53.2LJTertiary hospital (Armed forces)4Rai S P et al, 2007 [27]Ranchi2001–2004Newly diagnosed PTB patients76918.00.41.41.70.43.01.61.6LJTertiary hospital (Armed forces)5Jain A et al (a), 2008 [53]Lucknow2000–2002Combined PTB patients35337.42.00.30.66.019.329.011.0LJTertiary hospital6Jain A et al (b), 2008 [54]Lucknow2002–2004Combined PTB patients68638.229.720.717.827.719.825.513.2LJPrimary, Secondaryand Tertiary healthcare7Rawat J et al, 2009 [55]Dehradun2002–2006Prev. treated PTB patients18062.85.0057.257.2LJTertiary hospital8Datta B S et al, 2009 [56]Kashmir2003–2007Newly diagnosed PTB patients9105.70.9MGIT 960Primary, Secondaryand Tertiary healthcare9Mathuria J P et al (1), 2013 [38]Sawai Madhopur2004–2007Combined PTB patients4822.924.172.0814.5866.677.14LJDistrict...…”
Section: Resultsmentioning
confidence: 99%
“…2,4,5 However, earlier reports from Pune and Kashmir show a prevalence of 5.7%. 6,7 Thus, the prevalence of MDR-TB in different parts of India was observed at various magnitudes, which is also true globally.…”
Section: Discussionmentioning
confidence: 98%
“…This high proportion of XDR isolates can be explained as these two reports are from tertiary care reference centres. Dutta et al from Kashmir in the year 2007 reported about 15.3% of the MDR-TB isolates in their study as extensively drug resistant [4].…”
Section: Discussionmentioning
confidence: 90%
“…India is also witnessing an increase in the number of MDR cases being reported from many parts of the country [3,4]. An updated report from WHO in 2013 estimated prevalence of 3.6% MDR tuberculosis in newly diagnosed cases and 20% in previously treated cases [5].…”
Section: Introductionmentioning
confidence: 99%